Challenges and Effectiveness of Neurological Therapy: New Bobath Concept in Stroke Patient Rehabilitation - Suradinata, Yusuf Ardian; Zahra, Fany Jessica Gresia; Daneswara, Anindya Inas; Priyambudi, Ferosa Pradipta (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Semarang, 2024)
Background: This study investigated the effectiveness of the New Bobath Concept and virtual therapy in the rehabilitation of patients with neurological conditions, especially stroke. Method: A literature review of five scientific articles revealed that the New Bobath Concept is effective in improving motor function and functional activity of stroke patients. Result: The use of virtual therapy as a support for the New Bobath Concept has also been shown to accelerate the recovery process and increase patient participation. The analysis of scientific articles also highlighted the importance of developing more specific therapeutic strategies to maximize neuroplasticity adaptation and accelerate the recovery process. Conclusion: Suggestions are suggested to conduct further research with a wider sample, integrate the latest technology, and involve health experts in developing practical guidelines. These efforts are expected to improve the effectiveness of rehabilitation and the quality of life of patients with neurological conditions.